Diseño de una colección de bolsos con técnicas de tejido en paja toquilla con la colaboración de la asociación María Auxiliadora del cantón Sígsig - Ubillus Tenesaca, Carmen Lizbeth (2025)
Toquilla straw weaving in Ecuador is an emblematic artisanal manifestation, considered Cultural Heritage of Humanity. Its cultural and historical value lies in the technical skill required to work this vegetal fiber, especially in the Ecuadorian south, where this work is carried out. However, this artisanal activity is experiencing a significant decline due to various social, economic and innovation factors, which generates low profitability of the trade and a threat to the transmission of knowledge and the preservation of this intangible heritage. The project seeks to preserve the toquilla straw weaving techniques by creating bags that combine design and tradition. Its objective is to generate innovative, exclusive and quality pieces, which demonstrate how crafts can adapt to current fashion. In addition, it promotes collaboration between design and crafts, benefiting local communities, especially the artisans of the María Auxiliadora Toquilleras Association of the Sígsig canton, opening new business opportunities for them. The collection's design is aimed at meeting the needs of consumers through a qualitative study, as well as the application of interviews, focus groups and observation sheets of weaving techniques. The collection of bags seeks to transmit the richness of craftsmanship as part of the Ecuadorian cultural identity and its fusion with contemporary style, to explore new possibilities of applying natural fiber within the textile industry and accessory design. In this way, the artisans of toquilla straw open their possibilities to explore new business models that integrate their fabrics.